Successful Low-Cost Scaffold-Free Cartilage Tissue Engineering Using Human Cartilage Progenitor Cell Spheroids Formed by Micromolded Nonadhesive Hydrogel - Mellannie P. Stuart; Renata A. M. Matsui; Matheus F. S. Santos; Isis Côrtes; Mayra S. Azevedo; Karina R. Silva; Anderson Beatrici; Paulo Emílio C. Leite; Priscila Falagan-Lotsch; José M. Granjeiro; Vladimir Mironov; Leandra S. Baptista (Stem Cells International)
The scaffold-free tissue engineering using spheroids is pointed out as an approach for optimizing the delivery system of cartilage construct. In this study, we aimed to evaluate the micromolded nonadhesive hydrogel (MicroTissues®) for spheroid compaction (2-day culture) and spontaneous chondrogenesis (21-day culture) using cartilage progenitors cells (CPCs) from human nasal septum without chondrogenic stimulus. CPC spheroids showed diameter stability (486 μm ± 65), high percentage of viable cells (88.1 ± 2.1), and low percentage of apoptotic cells (2.3%). After spheroid compaction, the synthesis of TGF-β1, TGF-β2, and TGF-β3 was significantly higher compared to monolayer (p<0.005). Biomechanical assay revealed that the maximum forces applied to spheroids after chondrogenesis were 2.6 times higher than for those cultured for 2 days. After spontaneous chondrogenesis, CPC spheroids were entirely positive for N-cadherin, collagen type II and type VI, and aggrecan and chondroitin sulfate. Comparing to monolayer, the expression of SOX5 and SOX6 genes analyzed by qPCR was significantly upregulated (p<0.01). Finally, we observed the capacity of CPC spheroids starting to fuse. To the best of our knowledge, this is the first time in the scientific literature that human CPC spheroids were formed by micromolded nonadhesive hydrogel, achieving a successful scaffold-free cartilage engineering without chondrogenic stimulus (low cost).